Ortho-Quinone methides as key intermediates in cascade heterocyclizations. (August 2017) - Osipov, Dmitry V.; Osyanin, Vitaly A.; Klimochkin, Yuri N.
Abstract : Development of new methods of heterocyclic synthesis is still a topical issue. In this connection, the trend related to the use of highly reactive o -quinone methides for the synthesis and functionalization of heterocycles appears rather promising. Since most of o -quinone methides are unstable, the choice of precursors and generation conditions is highly important for subsequent transformations involving them. Various methods of generation of o -quinone methides and cascade hetero-cyclizations in which the formation of these compounds is a key step are surveyed in the review. The trends of using o -quinone methides in the synthesis of various heterocycles are analyzed and the heterocyclization reactions involving these compounds are classified. The bibliography includes 395 references.